Wasathiyyah Islam dan Pro-Eksistensi Komunitas NU-LDII di Desa Woromarto Kecamatan Purwoasri Kabupaten Kediri - Nasor, Moch. Azizi Saifun; Adib, Rama Riswan; Rofiqoh, Aqidatur (Canonia Religia, 2025)
This article discusses the phenomenon of pro-existence between religious communities as the key to building social harmony, particularly in Woromarto Village, Kediri Regency, which is inhabited by the NU and LDII communities. The main focus is to understand how dialogue in the village serves as a means of conflict resolution and as the foundation for creating a friendly and open society towards differences. This study uses a descriptive qualitative method by conducting in-depth interviews with the village head and community leaders. The findings show that interfaith dialogue in Woromarto Village occurs not only in theological realms but also in economic cooperation, mutual assistance, and joint activities. Additionally, the article refers to the thoughts of figures like Quraish Shihab on the importance of moderation as a critical step towards peace between civilizations. The geographical and economic conditions of Woromarto Village, which are dominated by farming livelihoods, further strengthen the dialogue between communities in daily activities. The article highlights the role of local figures, such as the village head and religious leaders, in fostering harmony and cooperation between religious communities. Patterns of interaction in daily life, especially during religious rituals, religious celebrations, and holidays, show that the people of Woromarto Village have created a cultural habitus that facilitates tolerance and harmony.